INTEGRATED INFORMATION ENVIRONMENT OF FAR EAST SUBDIVISION RAS AND FAR EAST FEDERAL UNIVERSITY: CURRENT AFFAIRS AND PROSPECTIVES FOR DEVELOPMENT - Vera V. Naumova; Leonid G. Vladimirov (Открытое образование (Москва))
The article covers the problems and projections of integrated informational environment of Far East federal university and Far East Subdivision RAS. The proposed virtual environment of the two institutions enables to attain fundamentally new opportunities in implementation of education and science activity of Far East federal university and Far East Subsidiary RAS. It is supposed that the received solutions can be used by other universities and scientifi c centers of the country.